ДОСЛІДЖЕННЯ СУЧАСНОГО СТАНУ РИНКУ ПРАЦІ В УКРАЇНІ - Todoruk, Sergy; Liubov, Vodianka; Лаврук, Іванна (My University, 2020)
В статті досліджено сучасний стан ринку праці в період глобалізації світової економіки. Баланс між попитом і пропозицією праці в Україні постійно змінюється внаслідок багатьох факторів, а саме: низькі заробітні плати, міграція населення, невідповідні умови праці, неврегульована ситуація на сході України, низький розвиток малого та середнього бізнесу, значна частка тіньового сектору, недостатня кількість робочих місць для кваліфікованих працівників, перенасичення окремих регіонів дешевою робочою силою, тощо. А також на основі отриманих статистичних даних вияснено в яких областях розмір заробітної плати найбільший, а де – не відповідає сучасним стандартам життя. Та незважаючи на це прослідковується позитивна динаміка щодо кількості зареєстрованих безробітних, починаючи з 2015 року їхня кількість швидко зменшується. Окрім того, охарактеризовано рівень заробітної плати за видами економічної діяльності та виявлено, що у фінансовій та страховій сферах оплата праці є найвищою, а у медицині та сфері надання соціальної допомоги найнижча, що, на нашу думку, є незаслужено. З огляду на вищесказане, слід акцентувати увагу на тому, що дану проблематику детально окреслено та поглиблено вивчено спираючись на статистичні дані державних органів.
RESEARCH ON THE CURRENT STATE OF THE LABOR MARKET IN UKRAINE
The current state of the labor market in the period of globalization of the world economy is investigated. The balance between labor supply and demand in Ukraine is constantly changing due to many factors, such as: low wages, population migration, inadequate working conditions, unsettled situation in eastern Ukraine, low development of small and medium-sized businesses, a large share of the shadow sector, insufficient number of jobs for skilled workers, oversaturation of individual regions with cheap labor, etc. It is found out in what areas the salary is the largest, and where - it does not meet the modern standards of living, on the basis of the obtained statistics. Nevertheless, there is a positive trend in the number of registered unemployed, since 2015 their number has been rapidly decreasing. In addition, the level of wages by type of economic activity has been characterized and it has been found that in the financial and insurance spheres wages are the highest, and in medicine and social assistance, the lowest, which, in our opinion, is undeserved. In recent years, the labor market in Ukraine has been deformed under the influence of many factors, namely: 1) the unsettled situation in eastern Ukraine as a result of which large numbers of refugees overwhelm certain regions with labor supply, which in turn leads to oversaturation of the labor market and an increase in the share of cheap labor; 2) nigration of the population caused by unfavorable ones the socio-economic situation of Ukraine, primarily due to inadequate working conditions at enterprises, low salaries, pensions, etc .; 3) there is no sufficient number of workers in the working professions, which are gaining popularity today due to insufficient demand for them; 4) the rapid rate of decline of the Ukrainian population and the increase in the share of the elderly, which in turn leads to a slowdown in the economic development of the country; 5) the presence of a shadow economy through which the state loses part of its gross domestic product annually; 6) massive reduction of small and medium-sized enterprises, which are the foundation of the economic structure of the state due to lack of competitiveness with other foreign firms in their products (services), high taxes, insufficient promotion of entrepreneurship by the state, etc .; 7) low level of investment activity, which is directly related to the complex legislative and regulatory framework governing the conditions of foreign investment.In view of the above, it should be emphasized that these issues are detailed and thoroughly studied based on the statistics of public authorities.
Keywords: заробітна плата; ринок праці; безробіття; зайнятість; тіньова економіка; wage; labour market; unemployment; employment; shadow economy